Efficacy of Various Final Irrigant Activation Procedures on Smear Layer Removal - A SEM Study - Amjed Majeed Khalaf; Biland M.S. Shukri (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: This in vitro study was intended to compare the removing efficacy of smear layer of the EndoVac , EDDY tip, XP - endo Finisher and conventional needle irrigation in palatal roots of extracted maxillary first molars, at the apical, middle and coronal levels by using scanning electron microscopy. Material and Method: The palatal roots of sixty recently extracted maxillary first molars were selected and divided into four groups (n=15) according to final irrigation agitation systems; EndoVac irrigation system,Eddy tip, XP - endo Finisher and conventional needle irrigation. Each root was prepared to 40/0.06 apical size with EDGEENDO X3 rotary files. Following splitting the root samples, single half of each sample was selected for examination under scanning electron microscope (SEM). The comparisons among irrigation activation devices were done using the Kruskal Wallis test and Mann-Whitney U test at 0.05 significance level. Conclusion: Within the limitations of the present study, no one of the tested systems can remove the smear layer completely. However, EndoVac system , Eddy tip and XP - endo Finisher remove significantly more smear layer than conventional needle irrigation at the apical third but there was no significant difference at middle and coronal thirds.